Modelling railway bridge asset management - Le, Bryant Linh Hai (2014)
The UK has a long history in the railway industry with a large number of railway assets. Railway bridges form one of the major asset groups with more than 35,000 bridges. The majority of the bridge population are old being constructed over 100 years ago. Many of the bridges were not designed to meet the current network demand. With an expected increasing rate of deterioration due to the increasing traffic loads and intensities, the management authorities are faced with the difficult task of keeping the bridge in an acceptable condition with the constraint budget and minimum service disruptions. Modelling tools with higher complexity are required to model the degradation of assets and the effects of different maintenance strategies, in order to support the management decision making process.